Editorial - Huggins, Jackie; Williams, Michael (The Australian Journal of Indigenous Education, 2001)
The Australian Journal of Indigenous Education in the next two editions will feature specialised subjects in matters of teaching and learning in the area of Aboriginal and Torres Strait Islander Education. This edition is featuring music - a rich and vital component of Indigenous cultures around the world.